A Koli eatery managed by women in Mazagaon Koliwada - Mumbai Archive Project Team (Jio Institute, 2024)
A Koli eatery managed by women is situated right outside the Mazagaon Dockyards. There are several roadside restaurants in Mazagaon Koliwada, such as this one. They offer a range of seafood-based dishes that are typical Koli fare. Popular dishes include the Bombil fried (Bombay Duck), Kolambi curry (Prawn), Sukka curry (Dry), Khekda masala (Crab), and Bangda curry (Mackerel).